Partitioning of assimilates in cotton from super-okra and normal leaves cultivars - de Souza, José Gomes; da Silva, Jorge Vieira (Pesquisa Agropecuaria Brasileira, 1991)
Leaf soluble protein content is higher, if not significantly, in super-okra than in normal leaves of cotton lines of cv. Louisiana. Amilolytic activity in leaves do not differ between lines but decrese significantly with age of leaf, whereas starch content stable with aging of leaf is smaller in the super-okra leaves and in super-okra carpels, seeds and roots. Invertase activity, probably linked with carbohydrate translocation, is higher in leaves of super-okra than normal, while soluble carbohydrates are in smaller amounts in carpels of the super-okra. It seems that super-okra with its much smaller leaf area than the normal line cannot supply enough assimilates to the plant for a good supply of carbohydrates to developping carpels and that breeding programs based on the utilization of reduced leaf area should aim to increase photosynthetic potential per unit leaf surface.